The significance of Partisan military courts for building the new Yugoslav government - Škoro Babić, Aida (Historical Thought, 2025)
World War II represents a significant milestone in terms of historical European and world space. In the territory of Bosnia and Herzegovina, as well as other south-Slavic countries, the ending of war brings the new government. Through the struggle and resistance against the occupying forces the new country with a new system was being created. In parallel with creating units of resistance (partisan units) there emerged the need for regulation of several issues related to the establishment of discipline and dealing with spies, deserters and perpetrators of serious crimes. The continuity of the former Yugoslavia was cut down and the new judiciary was established. The author discusses the issues and peculiarities of establishing military justice, which preceded the civil justice and its role in the creation of the new government.